Development of a differential load cell negating inertial force - Kim, Taeyong; Aulla Villacres, Marco; Shim, Jaehong; Kwon, Oh Sung; Kim, Ho Kyung (Measurement: Journal of the International Measurement Confederation, 2023)
Load cells, also referred to as force transducers, are widely used in various engineering fields for measuring forces and torques. When load cells measure the forces of moving specimens, the measured force includes the inertia of the specimen. However, in applications where the objective is to quantify the resultant force without the contribution of the specimen's inertia, additional sensors are required, which can result in reduced accuracy or inadequate measurement. To address the inertia coupling effect, this study proposes a new sensor, called a “differential load cell,” by combining two load cells using a novel Wheatstone bridge design. The primary load cell measures both the force of interest and the specimen's inertia, while the dummy load cell only measures the latter. The proposed Wheatstone bridge automatically negates the inertia, thereby addressing the coupling effect. Validation tests including wind tunnel experiments are conducted to examine the practicality and applicability of the differential load cell.
Keywords: Hybrid simulation; Inertial force negation; Inertial forces; Load cells; Real- time; Real-time aeroelastic hybrid simulation; Strain gauge load cell; Strain-gages; Wheatstone's bridge; Wind-induced force; Inertial force negation; Real-time aeroelastic hybrid simulation; Strain gauge load cell; Wheatstone bridge; Wind-induced force